2009
DOI: 10.1111/j.1399-0012.2008.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of liver graft function and regeneration by galactosyl‐human serum albumin (99mTc‐GSA) liver scintigraphy in adult living‐donor liver transplantation

Abstract: In LDLT, LHL15 has the potential to assess the graft function and predict the recipients' outcome. Graft function after LDLT may be related closely to the pretransplant MELD score, GRWR, and donor age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…Bilirubin is synthesized in the liver and released into the bile canaliculus, and in animal experiments conducted to evaluate excretory capacity by Kim et al 13 The present study also found no correlation between IR 20min and serum bilirubin level, but a signi cant difference was observed with IR 4min , suggesting that the shorter time after infusion better re ected the excretory capacity of hepatic cells. Previous literature indicates that ICG15 showed the strongest correlation with some biochemical liver functional data 7,9 , but this study could not reproduce these ndings. Likewise, this study showed only a slight correlation with HH15 when Tc-99m-GSA was used.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Bilirubin is synthesized in the liver and released into the bile canaliculus, and in animal experiments conducted to evaluate excretory capacity by Kim et al 13 The present study also found no correlation between IR 20min and serum bilirubin level, but a signi cant difference was observed with IR 4min , suggesting that the shorter time after infusion better re ected the excretory capacity of hepatic cells. Previous literature indicates that ICG15 showed the strongest correlation with some biochemical liver functional data 7,9 , but this study could not reproduce these ndings. Likewise, this study showed only a slight correlation with HH15 when Tc-99m-GSA was used.…”
Section: Discussioncontrasting
confidence: 72%
“…There are various analytical methods for the evaluation of hepatic function using Tc-99m-GSA, with the most widely used being the clearance index HH15 and the receptor index LHL15 . These indicators are easy to use and show good correlation with hepatic reserve 6,7 ; they have also been used recently in postoperative follow-up for hepatectomy, preoperative volumetry assessment of liver remnant functions 8,9 , and evaluation of hepatic functions after living donor liver transplantation 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…In LDLT, about 30–60% of the liver from the donor is harvested and transplanted to the recipient . The liver has a strong ability to regenerate, and it can become a nearly suitable size within a few months after transplantation . Previous reports have shown that patients who performed LDLT show smaller CL values than patients who received kidney or cadaveric liver transplantation, and the CL value increased with postoperative days (POD) to establish a steady state within 30 days of surgery .…”
mentioning
confidence: 99%
“…8 The liver has a strong ability to regenerate, and it can become a nearly suitable size within a few months after transplantation. [9][10][11][12] Previous reports have shown that patients who performed LDLT show smaller CL values than patients who received kidney or cadaveric liver transplantation, and the CL value increased with postoperative days (POD) to establish a steady state within 30 days of surgery. [13][14][15] Interestingly, in patients with a liver transplantation, the CYP3A5 genotypes in the liver and small intestine are derived from the donor and recipient, respectively.…”
mentioning
confidence: 99%
“…Compared with attenuation of the spleen, the attenuation of the liver graft was low in 31 and high isoattenuation in the other 632 recipients. Low graft attenuation was more commonly observed in recipients with IPF (19 of (12)(13)(14)(15)(16) suggested that abnormalities at indocyanine green plasma disappearance rate, maximum liver function capacity, technetium-99 m diethylenetriaminepenta-acetic acid-galactosyl human serum albumin ( 99 m Tc-GSA), and insulin-like growth factor can be associated with graft outcome. However, indocyanine green plasma disappearance rate can be affected by altered hepatic blood flow and can be affected by hemodynamic instability; it is not reliable for assessment of hepatic function in patients with severe jaundice.…”
Section: Clinical Outcomementioning
confidence: 99%